The features of translating of idioms in “three drops of blood” of S.Hedayat to english (Journal of Oriental Studies, 2019)
The article is oriented on the field of verbal crosscultural communication that assumes a studying of functioning of language as an intermediary at the description of foreignlanguage culture. In the article the possibilities of integration of the Persian idioms, used in S. Hedayat’s novel “Three drops of blood” into Englishlanguage texts focused on the description of the Iranian culture, are considered as well. The conducted article also includes the analysis of the ways of transferring of idioms made by two translators, and features and translation strategies of transferring the idioms used in the original of the work too. The practical importance of the current research consists in a possibility of using the results of the research for systematization of lexicon of the Persian and English languages, in translation theory, in lexicographic practice, in special courses according to the theory of crosscultural communication. Key words: idioms, phraseological units, cultural realities, translation, literary work, crosscultural communication.